Faktor-Faktor Utama Penyebab Human Error Dalam Kecelakaan Pada Operator Alat Berat Bergerak di Tambang Bawah Tanah PT. Freeport Indonesia - Triana Primadewi; Baju Widjasena; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2014)
Each did a job in the workplace, a person or a group of workers at risk of an accident or occupational disease. Human error was the cause of 80 % to 90 % of workplace accidents and is a major contributor to accidents. In underground mines PT. Freeport Indonesia, mobile heavy equipment accident at a 'top risk # 1' where a high number of events. Factors causing these accidents are often associated with human failure  was an indication of human error. Human error is also related to human factors occurs in a series of stages that include threats as a latent failure, situation awareness and action error as well as an active failure. The purpose of this study was to identified the main factors causing human errors that contributed to the incidence of accidents in the mobile heavy equipment operators at underground mines of PT. Freeport Indonesia. This research was an explanatory research with cross sectional and longitudinal retrospective study to investigate used a Human Factors Investigation Tool (HFIT). The number of samples in this study were 35 respondents. The results of this research conducted is a major factor in the discovery of each of these elements. Elements of occupational factors on threats approved by 24 operators (69%), the detection and perception of the elements of situation awareness experienced by 19 operators (54%), and the timing error of  the action elements committed by the 19 operators (54%). The statistic results with chi-square test indicates these three factors did not have a meaningful relationship, but has influences from one to another. Based on these findings, it is suggested that short- term improvements to give the referrals about safety to the workers and the long-term improvement is to create an integrated system to reduce it